Efek penghindaran pajak pada nilai perusahaan dengan pelaporan berkerlanjutan sebagai moderator - Yanti, Lili; Tanujaya, Kennardi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The value of the company can increase or decrease due to tax evasion. The increase in company value was caused by the takeover of potential state assets to shareholders. Companies carry out tax avoidance practices by reducing the amount of tax that should be paid to get high profits so as to increase the value of the company. Research on the topic of tax avoidance on company value still has different results from previous research so it still needs to be researched with the context in developing countries, namely in Indonesia. This study aims to test the effect of tax avoidance on company value and with the existence of sustainability reporting as a moderator. This study used quantitative data taken from companies listed on the Indonesia Stock Exchange from 2016 to 2020. Hypothesis testing using the panel regression method. The results showed that tax avoidance had no significant influence on the value of the company and the moderation of sustainability reporting on tax avoidance had a negative influence but not significant impact.